Entre “sobrados, lojas e funcos”: memória, identidade e representação literária na trilogia romanesca de Henrique Teixeira de Sousa - Pinto, Bruna Carolina de Almeida [UNESP] (2014)
We intend with this work to analyse the trilogy of novels Ilhéu de Contenda (1978), Xaguate (1987) e Na Ribeira de Deus (1992), by Henrique Teixeira de Sousa, in order to observe some of their compositional strategies of literary texts articulated around the same setting: the island of Fogo, of the cape verdean’s archipelago. The observation of works aimed at extracting the common elements and spontaneous everydayness of their interlocutors, as well as the recomposition of the environement circumscribed narrative in each phase, thus verifying the authenticity of the composition of these text as a trilogy. The emphasis on character memoirist of works studied, which are in total agreement with all of fiction Henrique Teixeira de Sousa, intended appreciate and emphasize the writing style of the author and their common approach to Cape Verdean literature themes